Finger Grip Relaxation Technique to Reduce Pain Scale in Post Appendictomy Surgery Patients: Literature Review - Siti Umaiyah; Rani Rahmawati; Zihan Hoerun Nisa; Dahlia Rachmawati; Shinta Arini Ayu; Fitri Anjani Bustami; Ikmal Maulidin; Resna Aranti (Jurnal Kesehatan, 2025)
Introduction: Appendectomy is an abdominal opening performed to remove the inflamed appendix. Post-appendectomy surgery will cause pain. Finger grip relaxation is one of the non-pharmacological methods that can reduce pain. This study conducted to determine how the finger grip relaxation technique affects the level of pain experienced by clients after appendectomy surgery. Method: Selected articles from the literature are reviewed and used in this study. Results: The use of finger grip relaxation techniques has been shown to be effective in reducing pain in post-appendectomy patients. Conclusion: The finger grip relaxation technique can help reduce pain intensity in patients who have undergone appendicitis surgery. Therefore, this technique can reduce physical and emotional tension, and the reflex points on the hands allow the body to feel relaxed.